Aromatic rutinosides from the aerial roots of Pandanus tectorius. (June 2020) - Sahakitpichan, Poolsak; Chimnoi, Nitirat; Thamniyom, Wassapol; Ruchirawat, Somsak; Kanchanapoom, Tripetch
Graphical abstract: Three new aromatic rutinosides were isolated from Pandanus tectorius . Highlights: Three new aromatic rutinosides were isolated from Pandanus tectorius. Aromatic compounds are mainly constituents from the aerial roots of Pandanus tectorius . It was the first time to report the constituents from Pandanus tectorius of Thai origin. Abstract: Three new aromatic rutinosides, including 2-methoxy-4-methylphenyl 1- O -rutinoside (1 ), 3, 5-dimethoxy-4-hydroxyphenyl 1- O -rutinoside (3 ) and ( S )-2-hydroxy-2-phenylethyl 1- O -rutinoside (6 ) were isolated from the fresh aerial roots of Pandanus tectorius . Additionally, the 12 known compounds were identified; 2-methoxy-4-hydroxymethylphenyl 1- O -rutinoside, cuneataside D, benzyl rutinoside, 2-phenethyl rutinoside, viridoside, 7, 8- threo -7-methoxysyringylglycerol, 7, 8- erythro -7-methoxysyringylglycerol, methyl caffeate, 3, 5-di- O -caffeoyl-quinic acid 1-methyl ether, 4, 5-di- O -caffeoyl-quinic acid 1-methyl ether, 3, 4-di- O -caffeoyl- epi -quinic acid methyl ester and hedyotol D 7"- O -β-D-glucopyranoside. The structure determinations were considered based on the physical data and the spectroscopic evidence including 1D and 2D NMR experiments.